Challenging current views on bile acid diarrhoea and malabsorption. Issue 2 (29th June 2017) - Kurien, Matthew; Thurgar, Elizabeth; Davies, Ashley; Akehurst, Ron; Andreyev, Jervoise
Abstract : Background: In 2012, the National Institute for Health and Care Excellence (NICE) assessed guidance (DG7) on the use of tauroselcholic ( 75 selenium) acid (also known as SeHCAT) for the investigation of diarrhoea due to bile acid malabsorption (BAM) in patients with IBS-D and in patients with Crohn's disease who have not had an ileal resection. NICE concluded that tauroselcholic ( 75 selenium) acid was recommended for use in research only. NICE will be reviewing the decision to update the guidance for tauroselcholic ( 75 selenium) acid, for these populations, in March 2017. Aim: Our aim is to summarise advances in BAM, also known as bile acid diarrhoea (BAD), and encourage clinicians to re-evaluate their understanding of this disorder. Approach: We review the prevalence, diagnosis and treatment of BAD/BAM. We describe the new evidence available since the original NICE review in 2012, and discuss the economic issues associated with failure to diagnose or to treat BAD/BAM accurately. Evidence update: There is new and compelling evidence available since DG7, which shows that tauroselcholic ( 75 selenium) acid scanning is a powerful tool in the diagnosis of BAD/BAM. We summarise published prevalence data (approximately 1% prevalence in the UK, as suggested by clinical practice diagnosis rates), and highlight that the true prevalence of BAD/BAM could be far greater than this. Conclusion: We present evidence that challenges current opinion about this disorder, and we commend both clinicians and health technology assessment (HTA) agencies for being open to arguments and new evidence in any future HTAs.